STRENGTHENING THE CAPACITY OF HEALTHY RICE MSMES THROUGH DIGITAL MARKETING AS A MODERN MARKETING STRATEGY - Solihin, Dede; Sofi’i, Imam; Septiani, Fauziah; Astuti, Widia; Gandung, Muhammad; Muharam, Hari; Pranowo, Agus Setyo; Wihartika, Doni; Yusnita, Nancy (Yayasan Education and Social Center, 2024)
Strengthening the capacity of healthy rice Micro, Small, and Medium Enterprises (MSMEs) and the growing market demand for healthy and quality products are essential. However, many healthy rice MSMEs still need help marketing their products effectively, especially in the digital era. One solution to increase competitiveness and expand the market is implementing digital marketing. This study analyzes how digital marketing can be an effective marketing strategy for healthy rice MSMEs to increase their business capacity. The method used in this study is a qualitative approach with case studies on several healthy rice MSMEs that have started implementing digital marketing. Data collection techniques were conducted through in-depth interviews with MSME owners and observation and analysis of the digital marketing content used. The study results show that using digital marketing, such as social media, marketing through websites, and e-commerce platforms, can increase product visibility, expand the market, and strengthen relationships with consumers. In addition, implementing the right digital marketing strategy can improve sales and competitiveness of healthy rice MSMEs in the modern market. This study suggests that healthy rice MSMEs should optimize digital marketing as part of their marketing strategy